2012
DOI: 10.1371/journal.pone.0052295
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Synapses Utilize Multiple Synaptic Ribbons in the Mammalian Retina

Abstract: In the mammalian retina, bipolar cells and ganglion cells which stratify in sublamina a of the inner plexiform layer (IPL) show OFF responses to light stimuli while those that stratify in sublamina b show ON responses. This functional relationship between anatomy and physiology is a key principle of retinal organization. However, there are at least three types of retinal neurons, including intrinsically photosensitive retinal ganglion cells (ipRGCs) and dopaminergic amacrine cells, which violate this principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…This spectral behavior is typical of M5 ipRGCs (Stabio et al, 2018 cells. This raises the possibility that bipolar inputs to the outer arbor of M6 cells might be the target of the same unusual ON channel input as M1 ipRGCs and dopaminergic amacrine cells (Dumitrescu, Pucci, Wong, & Berson, 2009;Hoshi, Liu, Massey, & Mills, 2009;Kim et al, 2012). Among the targets of ectopic ON bipolar en passant synapses in rabbit retina are outer (distal) dendrites of the "bistratified diving cell" (Hoshi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This spectral behavior is typical of M5 ipRGCs (Stabio et al, 2018 cells. This raises the possibility that bipolar inputs to the outer arbor of M6 cells might be the target of the same unusual ON channel input as M1 ipRGCs and dopaminergic amacrine cells (Dumitrescu, Pucci, Wong, & Berson, 2009;Hoshi, Liu, Massey, & Mills, 2009;Kim et al, 2012). Among the targets of ectopic ON bipolar en passant synapses in rabbit retina are outer (distal) dendrites of the "bistratified diving cell" (Hoshi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One central assumption was that BC axon terminals are the source of glutamate release in the IPL. However, some On BCs feature ectopic synapses along their axon (Dumitrescu et al, 2009;Kim et al, 2012) which might contribute to observed On responses in the Off sublamina ( Fig. 2d,g 2 ).…”
Section: Sources Of Glutamate Release In the Iplmentioning
confidence: 99%
“…Recently, confocal analyses with an antibody to CtBP to label ribbon synapses revealed that ON‐type cone bipolar cells make ectopic synapses with the specific types of ganglion cells, such as melanopsin ganglion cells and dopaminergic amacrine cells in the rabbit and mouse retina at the stratum 1 of the IPL (Hoshi et al, ; Dumitrescu et al, ). More recent ultrastructural analyses have demonstrated that not only stratum 1, but more proximal parts of axonal processes of ON‐type cone bipolar cells also had multiple ectopic synaptic sites (Kim et al, ; Lauritzen et al, ). Furthermore, a calcium imaging study with SyGCaMP2 detected the ectopic signals in in vivo zebrafish retina (Dorostkar, Dreosti, Odermatt, & Lagnado, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, specific types of ganglion or amacrine cells stratify into stratum 1 of the IPL receive ectopic synapses (van Haesendonck & Missotten, ; Hoshi, Liu, Massey, & Mills, ; Dumitrescu, Pucci, Wong, & Berson, ; Kim et al, ) or even more broadly in sublamina a (Lauritzen et al, ). Here, we show ectopic synapses from the Mb1 bipolar cell to this displaced ganglion cell that stratified into stratum 1 of the IPL.…”
Section: Introductionmentioning
confidence: 99%